Mediating role of social media marketing adoption between technological support, organisational support, government support and competitive intelligence towards SMEs performance. - Muhammad Faizal Samat. (2018)
Business environment in Malaysia has become more competitive due to the advancement of technology and globalization. The rapid evolution of technology has encouraged many companies to use social media as a medium of promoting their products and service. This includes small and medium enterprises (SMEs). Small and medium enterprises (SMEs) have so long devised various marketing strategies in order to penetrate the advertisement clutter in social media marketing and improve their performance. Past studies have shown that using information and communication technologies such as social media can improve SMEs performance as well. However, the adoption of social media marketing relies on the process of information collection and analysis by the owner-managers of SMEs. Most of the SMEs have their own websites but use them primarily as an information tool only. Thus, this study investigated the mediating role of social media marketing adoption between technological support, organisational support, government support and competitive intelligence towards SME performance. The theoretical framework of this study has been supported by two underpinning theories which are Resource-based View (RBV) and Diffusion of Innovation (DOI), and supported by Technology, Environment and Organisation (TOE) framework. This study has been carried out in the East Coast of Malaysia that covers the area of Kelantan, Terengganu and Pahang. A quantitative research by using questionnaire survey method was employed in this study. A total of 1920 owner/managers SMEs were randomly selected and questionnaires were sent through mail. 339 responses were returned and found usable for the final analysis using the structural equation model partial least square (SEM-PLS). The findings revealed that technological support, government support and competitive intelligence have significant and positive relationships with SME performance. However, organisational support does not have a significant relationship with SME Performance. This is due to the fact that size of the organization does affect this relationship. In addition, the study confirmed the mediating effect of social media marketing adoption on the relationship between technological support, organisational support, government support and competitive intelligence, and SME performance do exist. Finally, the study’s theoretical and practical implications as well as the limitations and directions for future research were provided and discussed.